2011
DOI: 10.1007/s10787-011-0097-1
|View full text |Cite|
|
Sign up to set email alerts
|

Acamprosate modulates experimental autoimmune encephalomyelitis

Abstract: Acamprosate and other taurine analogs have a potential for future MS therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The present piece of work suggests that homotaurine supplementation in aMCI individuals carrying APOE ε4 has a positive consequence on episodic memory loss due, at least in part, to homotaurine anti-inflammatory effects targeting IL-18. While some studies highlighted the potential of homotaurine and its derivatives to benefit patients with MCI (Martorana et al, 2014 ; Spalletta et al, 2016 ), and to modulate inflammation in mouse models (Sternberg et al, 2012 ), this is the first evidence ever provided that homotaurine supplementation holds anti-inflammatory properties associated with memory improvement in patients with cognitive impairment.…”
Section: Discussionmentioning
confidence: 98%
“…The present piece of work suggests that homotaurine supplementation in aMCI individuals carrying APOE ε4 has a positive consequence on episodic memory loss due, at least in part, to homotaurine anti-inflammatory effects targeting IL-18. While some studies highlighted the potential of homotaurine and its derivatives to benefit patients with MCI (Martorana et al, 2014 ; Spalletta et al, 2016 ), and to modulate inflammation in mouse models (Sternberg et al, 2012 ), this is the first evidence ever provided that homotaurine supplementation holds anti-inflammatory properties associated with memory improvement in patients with cognitive impairment.…”
Section: Discussionmentioning
confidence: 98%
“…Mice were subjected to 30 minutes of transient focal cerebral ischemia as described below followed by intraperitoneal treatment with either acamprosate (Sigmal-Aldrich, Taufkirchen, Germany; solved in NaCl) or standard saline (control) during reperfusion, at 3, 6, 9, 12, and 24 hours after stroke. Referring to previous studies, [15][16][17][18][19][20] mice received a modified injection protocol with a single intraperitoneal injection of acamprosate at a dose of 400 mg/kg bodyweight (BW). To exclude toxic side effects of acamprosate after high dosage bolus application, analysis of potential weight loss and blood count analysis was performed 1 day before stroke induction as well as on days 7 and 14 after stroke ( Table 1).…”
Section: Experimental Paradigmmentioning
confidence: 99%
“…[12][13][14] In addition to the aforementioned effects during alcohol dependence, experimental evidence suggests a therapeutic role for acamprosate in neurologic disorders such as multiple sclerosis. 15 Since activation of the glutamatergic system and stimulation of NMDAR are decisive in the development of cerebral ischemia as stated afore, a single study analyzed the therapeutic potential of acamprosate in a rat model of cerebral ischemia. 16 Although limited and descriptive in its nature, this study remained the only one demonstrating neurologic recovery on day 3 after stroke after pretreatment with acamprosate.…”
Section: Introductionmentioning
confidence: 99%
“…Topiramate, however, primarily affects other ion channels (e.g., sodium and calcium channels) and enzymes 22 , 23 and vigabatrin does not bind to GABA-Rs but rather inhibits GABA transaminase 23 , and both drugs have multiple adverse effects. Other studies have shown that the anti-alcohol dependence drug acamprosate, which has structural similarities with GABA, can limit EAE 24 , but recent studies indicate that acamprosate does not act directly through GABA A -Rs 25 , 26 . Benzodiazepines and barbiturates are BBB-permeable GABA A -R positive allosteric modulators that can potentiate the opening of GABA A -R chloride channels, but only after a GABA A -R agonist opens the channel, and these drugs can be addictive.…”
Section: Introductionmentioning
confidence: 97%